All-Cause Mortality After the Great East Japan Earthquake in Fukushima Prefecture: Trends From 2009 to 2016 and Variation by Displacement. (6th December 2021) - Tsuboi, Satoshi; Mine, Tomosa; Kanke, Satoshi; Ohira, Tetsuya
ABSTRACT: Objectives: On March 11, 2011, a magnitude 9 earthquake (the Great East Japan Earthquake) occurred off the east coast of Japan. After the Fukushima Daiichi Nuclear Power Plant accidents, as of 2016, people were not allowed to live in the 6 districts (Tomioka, Okuma, Futaba, Namie, Katsurao, Iidate) in Fukushima Prefecture. In the present study, we aimed to evaluate the long-term effects of displacement on all-cause mortality in Fukushima Prefecture. Methods: Data regarding population and deaths from 2009 to 2016 in Fukushima Prefecture were obtained from the governmental statistics. The age-adjusted all-cause mortality were compared among the 4 areas in Fukushima Prefecture; the Eastern, Middle, Western, and Displacement areas. Results: The age-adjusted all-cause mortality rates in the Eastern and Displacement areas were higher than in the other 2 areas from 2009 to 2011. During the period from 2012 to 2016, all-cause mortality in the Displacement area decreased to the lowest, while the morality in the Eastern area remained the highest. Conclusions: Against all expectations, after the earthquake, all-cause mortality in the Displacement area was continuously lower than in the rest of the Fukushima Prefecture. Following disasters, long-term monitoring should be organized to meet local health-care needs.